NURTURING TECHNOLOGY AND INNOVATION FOR SUSTAINED GROWTH: ROLE OF UNIVERSITIES - Pattnaik, Pinaki Nandan; Patnaik, Bignya (Journal of Business And Entrepreneurship, 2022)
At a theoretical level, the triple helix model has been developed and understood by scholars for the last two decades. The interdependence and the interplay among the government – academia-industry, both at a theoretical as well as empirical level is well established. Researchers have focused on different stages of the triple helix model, wherein the first stage is denoted as the statist model. This paper tries to understand and express the application of the Triple Helix Model in the case of T-Hub, an incubator in India and its success due to its interplay with universities. An embedded single case study approach has been used to understand the interaction between local government, academic institutions, and the industry. The case shows the strategic application of the Triple Helix Model for encouraging entrepreneurial activity at Hyderabad by the Government of Telangana for optimum results by bringing together universities, industry, and the state apparatus.